The Effect of Cllaborative-Learning Strategy on Students Ability to Write Narrative Essay - Rahmawaty, Kurnia; Sabarun, Sabarun; Normuliati, Sri (Journal of English Language and Education, 2024)
This article explores the effect of collaborative learning strategies on students' narrative writing. A quasi-experimental study involving two groups showed that the experimental group (m=0.5), demonstrated a noteworthy enhancement on their writing abilities in contrast to the control group. This suggests that collaborative learning strategies enhance writing abilities and increase active participation in learning. The study emphasizes the importance of innovative and interactive learning strategies, especially in language teaching, for optimizing students' narrative writing abilities. The experimental class's average pre-test scores were 72.42, whereas the control groups were 65.67. Following therapy, the average scores of experimental class's roses to 86.13, while the control class's average was 79.33. The result revealed that the p-value (.000) is less than 0.05. The alternative hypothesis (Ha) uses statistical analysis with SPSS and t-test, shows a significant increase in narrative knowledge in the experimental group.